A Brief Review of Ground Penetrating Radar Investigation Results of Ice Caps on Galindez, Winter and Skua Islands (Wilhelm Archipelago, Antarctica) for the Period April 2017 – January 2019 - Chernov, A.P.; Lamsters, K.; Karušs, J.; Krievāns, M.; Otruba, Yu.S. (Український антарктичний журнал, 2018)
This paper represents results of GPR surveying of the ice caps on Galindez (–64.24716W; –65.24992S), Winter (–64.25954W; –65.24944S) and Skua (–64.26530W; –65.25309S) islands (Wilhelm Archipelago, Antarctica) for the period April 2017 — January 2019. The main objectives were identification of the ice layering, monitoring of interglacial heterogeneities (crevasses, interglacial channels and voids) and measurements of the ice thickness. В роботі представлені результати георадарних досліджень льодовиків на островах Галіндез (–64.24716W; –65.24992S), Вінтер (–64.25954W; –65.24944S) та Скуа (–64.26530W; –65.25309S) (архіпелаг Вільгельма, Антарктика). Головною метою досліджень було виявлення шаруватої будови льодовиків, моніторинг внутрішніх неоднорідностей (тріщини, внутрішні канали та пустоти) та вимірювання товщини льоду.